(v-2w-2)(v-4)=0

Simple and best practice solution for (v-2w-2)(v-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-2w-2)(v-4)=0 equation:


Simplifying
(v + -2w + -2)(v + -4) = 0

Reorder the terms:
(-2 + v + -2w)(v + -4) = 0

Reorder the terms:
(-2 + v + -2w)(-4 + v) = 0

Multiply (-2 + v + -2w) * (-4 + v)
(-2(-4 + v) + v(-4 + v) + -2w * (-4 + v)) = 0
((-4 * -2 + v * -2) + v(-4 + v) + -2w * (-4 + v)) = 0
((8 + -2v) + v(-4 + v) + -2w * (-4 + v)) = 0
(8 + -2v + (-4 * v + v * v) + -2w * (-4 + v)) = 0
(8 + -2v + (-4v + v2) + -2w * (-4 + v)) = 0
(8 + -2v + -4v + v2 + (-4 * -2w + v * -2w)) = 0

Reorder the terms:
(8 + -2v + -4v + v2 + (-2vw + 8w)) = 0
(8 + -2v + -4v + v2 + (-2vw + 8w)) = 0

Reorder the terms:
(8 + -2v + -4v + -2vw + v2 + 8w) = 0

Combine like terms: -2v + -4v = -6v
(8 + -6v + -2vw + v2 + 8w) = 0

Solving
8 + -6v + -2vw + v2 + 8w = 0

Solving for variable 'v'.

The solution to this equation could not be determined.

See similar equations:

| 2=200/w^2 | | 2x+8+x+1=0 | | 3(20x+50)=510 | | 5x+24(x-2)=184 | | -5x+40=6x-(70) | | 40x+7=40d+34 | | (27x^4)+3p=2p | | 2m+3=2m-3 | | 6r^3+2r^2-48r= | | 3y-7=80 | | H-3=12 | | (3v-w-2)(7v+6)=0 | | 4(x+2)+3(x-6)=-3 | | 5x-20=x-2.4 | | 5a/24÷1/12 | | 9x/-102/3 | | -5t=-35 | | ln[(x-9)/((x^(2)-81)^(5))]^((2)/(5)) | | (3x+21)=(6x+15) | | 7p+21+9=10p-10-3p | | X^4-5x^2=-6 | | 2x^2+4x=240 | | 3x+5y=102 | | X+25+3(x)=435 | | 4(x-5)=-1.2x-1.2 | | (2x+4)2=240 | | D-4/9=-1/12 | | 85-x=20+x | | 5x(200)+10x=1630 | | 3/5x-6=6 | | 3/7m-1/3=2/3 | | .4(x-5)=-1.2x-1.2 |

Equations solver categories